Telaah Kritis Konstruksi Eksistensialisme dalam Teologi Antroposentris Ḥasan Ḥanafī - Masduri Masduri (Islamika Inside: Jurnal Keislaman dan Humaniora, 2018)
Anthropocentric theological reconstruction of Ḥasan Ḥanafī introduces us a set of humanity themes as a stand point to build and develop human’s religious-spiritual reason in order to respond to spiritual emptiness of the West and material desolation of the East. Human beings possess what so-called authenticity of actions. It is—within Ḥanafī’s anthropocentric theological reconstruction—termed as independent human; a human who has independence in every action and makes the Islamic theology as the basis of his/her spiritual and practical values. Critical reading through the theory of hermeneutics promulgated by Jurgen Habermas brings this article to a finding of epistemological correlation between the independent human (within Ḥanafī’s anthropocentric theological reconstruction) and the construction of thought the West’s existentialism philosophy. Critical-constructive reading of this article puts Ḥanafī as a theistic-existentialist philosopher along with Islamic theology as his fundamental basis.